Youth Mainstreaming Strategy in the Development of Tourism Villages Through BUM Desa in Malang Regency - Dwinugraha, Akbar Pandu; Kismartini, Kismartini; Astuti, Retno Sunu; Aziz, Nana Abdul (Universitas Sultan Ageng Tirtayasa, 2025)
Formulating a youth mainstreaming strategy in village tourism management through village-owned enterprises (BUM Desa) is the purpose of this study. The type of qualitative research using process hierarchy analysis is used in this study. Data collection is carried out through three stages and produces a possible strategic direction to take. The results of this study found that there are five alternative strategies for youth mainstreaming in village tourism development. SWOT analysis shows that the elements of strengths and opportunities must be optimized through digital marketing diversification strategies and human resources capacity building. Meanwhile, internal and external problems must be addressed by increasing collaboration and making policies that support the sustainable management of BUM Desa. This research has limitations in the number of informants used with expert judgment considerations; in the future, hopefully, the next research will be more representative of the number of BUM Desa in Malang Regency.